The Impact of Using VocBlast to Learn Technical Vocabulary at Tertiary Level - Mohd Amir Izuddin, Mohamad Ghazali; Zuraina, Ali (Novelty Journals, 2017)
Recently, there has been a rapid development of mobile applications (apps) for language learning purposes. An app namely VocBlast is designed to provide new learning experiences for engineering students to improve knowledge in technical vocabulary. The paper investigates the students’ viewpoints about the impact of using VocBlast to learn technical vocabulary between genders. 68 students from University Malaysia Pahang (UMP) were selected as samples using purposive random sampling method. A Likert-type questionnaire was employed to gauge students’ perceptions in using VocBlast. Using independent samples t-test, the results of the study revealed that there was no significant difference between genders on the impact of using VocBlast to learn technical vocabulary. This suggests that both genders equally perceived VocBlast as a useful vocabulary mobile app to learn technical vocabulary. In terms of learning pedagogy, the study extends the knowledge of mobile learning by providing insights on engineering students’ positive attitude in adopting vocabulary mobile app to learn technical vocabulary.